(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The topic of this paper is an experimental analysis of the dynamic behaviour of stays of an existing footbridge focusing on determination of the tensile forces in stays. The examined structure was the footbridge across the Vltava river in Lužec nad Vltavou. It is a cable-stayed footbridge, the horizontal load-bearing structure consists of UHPC components, which are prestressed by a pair of external cables. The horizontal load-bearing structure is suspended on a 39.85 m high A-shaped steel pylon by means of a system of 17 pairs of stays. As a part of the work the tensile forces in stays were determined using the vibration frequency method. The method is based on the knowledge of natural frequencies of the stays, which were investigated by the experimental analysis.